Data, technology, and the future of play : understanding the smart toy landscape - Athavale, Meghan (O'Reilly Media, 2016)
Toys are becoming increasingly smarter. Once merely objects of play, today's toys often act as agents of play, guiding kids toward learning through interactivity and feedback. As this O'Reilly report explains, smart toys not only employ sophisticated algorithms, but also share data and get updates via the cloud. What are the implications of a toy that, instead of fostering open-ended play, now becomes the playmate? Author Meghan Athavale takes you on an objective tour of today's smart toys: how they've evolved from their roots in the early '90s, as well as the ethics, risks, and promise they carry with them. Though it's still early days, digital toys are already changing how children learn and socialize. They're also likely to have a permanent impact on our brains and our culture. In this report, you'll explore: Three feedback loops that guide the behavior of a smart toy over its lifetime Privacy concerns about a smart toy's ability to "converse" with children by collecting and storing conversations The risk of children becoming socially withdrawn and addicted to technology due to increased use of smart toys Benefits of smart toys, including the ability of the machines to learn from users and provide customized education Predictions for how data and technology will change the nature of play and toys--including connected play and immersive environments